1961
DOI: 10.1111/j.1423-0410.1961.tb03149.x
|View full text |Cite
|
Sign up to set email alerts
|

A Weak Example of the Blood Group Antigen A

Abstract: Summary A weak form of the antigen A is reported in a healthy adult. It does not appear to correspond with any other weak form of A previously reported, except perhaps with that of Weiner, Race and Sanger. Centrifugation methods with antisera from donors injected with group specific substances are essential for the reliable demonstration of this antigen which, under these circumstances, gives a typical microscopic picture of isolated small clumps of cells set in a sea of unagglutinated cells. No symbol is used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
7
1

Year Published

1961
1961
1973
1973

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 7 publications
0
7
1
Order By: Relevance
“…The Annn variant, however, has not been found to differ in a substantial way from published descriptions of the phenotype Aend [12,20,21,30].…”
Section: Discussionmentioning
confidence: 76%
“…The Annn variant, however, has not been found to differ in a substantial way from published descriptions of the phenotype Aend [12,20,21,30].…”
Section: Discussionmentioning
confidence: 76%
“…The Afmn variant, however, has not been found to differ in a substantial way from published descriptions of the phenotype Aend [12,20,21,30,31], Originally stated to be nonagglutinable by anti-A or anti-A + B sera in the tube sedimentation technique, group Aend cells were later found to form microscopically demonstrable agglutinates with immune anti-A or anti-A + B sera from stimulated donors, if a tube centrifugation procedure was used. Group Aend persons secrete H but not A substance, as do the Finnish group A variant cases, and anti-Aj agglutinins are present in their sera.…”
Section: Discussionmentioning
confidence: 86%
“…Moore et al [3,4] reported two similar and probably identical phe notypes in 1961 ; Jacobowicz et al [2] found a further example in 1963. Now that four examples have been reported, in two of which [4,9] the variant was shown to be inherited, to leave this phenotype unnamed is to invite confusion.…”
mentioning
confidence: 99%
“…The use of letters for such variants was suggested by Weiner et al [9] ; the letters themselves are derived from the propositus' name in the first report [9]. The serological characteristics of this phenotype are briefly thus: 1. a) Using a sedimentation technique, no reactions are given by anti-A from donors who have not been injected with group specific substance [3,9]. b) Using the same technique, a variable proportion of anti-A from "stimulated donors" produce very weak agglutination [4].…”
mentioning
confidence: 99%
See 1 more Smart Citation